Classification of errors in the process of observation - D.G, Sharipova; N.X, Bozorova; Z.A, Salixova; D.P, Xikmatova; L.X., Bobomurodova (International Journal of Psychosocial Rehabilitation, 2020)
In article was written about classification of errors in the process of observation of students and teachers. The main error types in observation and correcting ways of these errors.